A New Geometric Reasoning Technique for Hot Spot Prediction in Sand Casting - Pao, William (IEEE, 2005)
In this paper, we report the use of medial axes transformation technique to predict temperature pro- ¯le and hot spots in solidifying castings. In essence, we proposed a very simplistic yet comprehensive tem- perature interpolation algorithm which can solve the solidi¯cation problem qualitative and quantitatively. The method has the advantages of both the geometric reasoning technique and the conventional numerical simulation. We illustrate the feasibility of the pro- posed temperature interpolation technique by com- paring its solutions with both pure geometric reason- ing technique and the ¯nite element method.